An Empty Graveyard: The Victims of the 1946 AOA DC-4 Crash, Their Final Resting Place, and Dark Tourism - Daly, Lisa Michelle (2018)
In 2013, archaeologists succeeded in locating a plane crash that had been presumed buried based on local stories. The aircraft had crashed into a steep hill, subsequently known as Crash Hill. On the summit is a deteriorated memorial which resembles a cemetery, marking the thirty-nine people who died in the 1946 tragedy. This memorial has been a spot of pilgrimage for family and an attraction for adventure seekers. This draw to dark tourism sites is not uncommon but since archaeologists shared their finds with the public through social and local media, many of those visitors are drawn to the crash site instead of the memorial. This is a problem as there are possibly mass graves at the crash site, and visitation can potentially disturb those remains. This article argues for caution when discussing finds publically and for the repair and restoration of the memorial at the top of the hill to fill the want to visit a site of tragedy without disturbing the actual crash site.